Managing Educational Resources for IPAS Instruction in Primary Schools: Strategies for Implementing the Merdeka Curriculum - Friani, Devi Anggi (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
The implementation of the Merdeka Curriculum in Indonesia introduces significant pedagogical shifts, particularly in how educational resources are managed and utilized in primary schools. One of the key components of this curriculum is IPAS (Ilmu Pengetahuan Alam dan Sosial), an integrated subject combining science and social studies aimed at promoting contextualized, inquiry-based learning. This study explores the strategies employed by SDN Gondang, a public primary school in East Java, in managing educational resources to support effective IPAS instruction under the Merdeka Curriculum framework. Employing a qualitative case study approach, data were collected through semi-structured interviews with teachers and school leaders, direct classroom observations, and analysis of instructional documents. The findings reveal that the school implements various adaptive strategies, including collaborative development of contextual teaching materials, integration of local environmental content, use of simple digital media, and peer mentoring among teachers. Despite facing limitations such as infrastructure gaps and varying levels of teacher preparedness, SDN Gondang demonstrates innovative and resourceful practices aligned with the curriculum’s principles. The study highlights the importance of leadership, professional collaboration, and continuous capacity building in enabling effective educational resource management for curriculum reform. These insights offer valuable implications for schools across similar contexts seeking to strengthen the implementation of integrated subjects like IPAS.